The social side of politics - Hartmann, Douglas; Uggen, Christopher (New York, NY : W.W. Norton & Company, 2014)
Overview: Assembling the most provocative new thinking on politics and political processes. This first volume of The Society Pages series focuses on politics. Drawn largely from feature content, posts, and exchanges provoked by the elections of 2012, the chapters are organized into three main sections. "Core Contributions" exemplifies how sociologists and other social scientists think about otherwise familiar political phenomena like power, polling, and social movements. Chapters in the "Cultural Contexts" section draw out the political content and implications of cultural realms-from religion and race, to sports, humor, and new media technologies-that are often ignored or taken for granted. And the "Critical Takes" rubric gathers pieces on inequalities embedded in and reproduced through the political system, how sociological tools and insights are employed in the public sphere, and the role of government in shaping society through public policy.
Series preface / Douglas Hartmann and Christopher Uggen -- Introduction / Douglas Hartmann and Christopher Uggen -- Changing lenses: behind the political process / Douglas Hartmann with Wing Young Huie -- Part 1: Core Contributions: -- Power, sociologically speaking / Vincent J. Roscigno -- Polling, politics, and the populace according to Goren, Schuman, and Smith / Kyle Green -- Social fact: those who can, vote? / Deborah Carr -- Movements + elections = democracy / Steven Buechler -- Obama era, the 2012 election, and systemic racism / Joe R Feagin -- Part 2: Cultural Context: -- Social functions of religion in American political culture / Joseph Gerteis -- Politics and sports: strange, secret bedfellows / Kyle Green, Douglas Hartmann -- Facebook's impact on American politics / Jose Marichal -- Laughter and the political landscape / Sarah Lageson, Sinan Erensu, Kyle Green -- Part 3: Critical Takes: -- Paradoxes of Black Republicans / Corey Fields -- Let Herman be Herman: Republican presidential candidate Herman Cain and the utility of blackness for the political right / Enid Logan -- Perils of transcendence / Andra Gillespie -- Sociology of silver / Andrew Lindner -- Joe Soss on American poverty governance, as it is and as it might be / Sarah Shannon -- Discussion guide and group activities -- About the contributors -- Index.
Includes bibliographical references and index.
Keywords: Political sociology; Political sociology